Profissão professor de educação física: história sobre: Thales de Assis Martins - Barbosa, Sergio Sérvulo Ribeiro (2015)
This work brought as a theme: PROFESSION TEACHER OF PHYSICAL EDUCATION: STORIES ABOUT: THALES DE ASSIS MARTINS, whose objective was to investigate the local history, retracing the history and memory of the knowledge and practices of a teacher of Physical Education, analyzing the context, the place , space, difficulties, problems, strengths, and especially what was the meaning in the office to be a physical education teacher in Uberlandia in the period 1940 to 1990. It sought to define initially the history of Physical Education in Brazil, in Minas Gerais and in Uberlandia locus of research and teacher professional development chosen for this study. This study is in the field of historiography of Education findings by mapping the area of Physical Education, we chose cultural history as theoretical framework, thus enabling cross sources of oral history of life with the documentary and bibliographic sources. The period of this research takes us back to memories of countless imposition of standards that have been imposed by the military. The thesis is organized into eight parts, with the first part presents the introduction, the second brings the first chapter that looks at ways to conduct this research revealing the methodological, who have called, methodological routes: intersecting paths. The third part brings the history of physical education in Brazil. The fourth part brings Occupation PE teacher. The fifth brings the findings of life and Thales teaching profession. The sixth part of the continuity and the fourth call of THALES IN THALES. The seventh part presents the final considerations, and the eighth and final part brings the references so important for this study. In relation to the proposed goals to his life story and professional demonstrated the various historical moments experienced by the Brazilian Physical Education, since its inception the militaristic nature of beliefs as a hygienist in the constitution of the area process, the creation of short courses for immediate training of trainers / instructors, and normalists to act in primary schools throughout the country.